ID: 144. Issue 1 (November 2015) - Harari, Daniel; Orr, Irit; Rotkopf, Ron; Baranzini, Sergio; Schreiber, Gideon
<x xml:space="preserve">Abstract</x> We analysed gene expression microarray data from whole blood samples from 228 multiple sclerosis (MS) patients either untreated or treated with one of three alternative commonly used interferon beta (IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pxq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β)</alternatives> disease modifying drugs: Avonex® (<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r2z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />×</alternatives>1 weekly), Betaseron® (every second day) or Rebif® (<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r2z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />×</alternatives>3 weekly). Patient injections were not timed to coordinate with sample collections, thus providing a global transcriptomic profile for each population of patients studied. Three hundred and fifty-one genes were significantly differentially expressed by at least one of the IFNβ drugs. Despite the different drug sources with distinct injection and dosage protocols, a striking similarity was found in the identity and functional classes of the differentially expressed genes induced. Using the 25 most-upregulated genes, we defined a robust IFNβ gene expression signature that quantifies the IFN activation state per blood sample collected irrespective of the type of IFNβ therapy. This 25-gene signature also defined basal IFN activation states among untreated MS patients, which differed among individuals but remained relatively constant per patient with time. The maximum drug-induced IFN-activation state was similar for all three drugs despite a 1.7–2.0-fold diminished average effect for Avonex. This and a more erratic effect of Avonex per patient across longitudinal measurements is likely a result of its reduced injection frequency. In summary, we have defined a robust blood-derived type I IFN gene signature from MS patients. This signature could potentially serve to generically quantify the systemic Type I IFN activation status for any other clinical manifestation, inclusive of other autoimmune diseases.